CoVisualStudio : converting MS Visual Studio into a real-time collaborative programming development environment - Lim, Jun Jie. (2013)
This is the age of mobile devices. Smartphones and tablet devices have dominate the market. They give rise to a new market of mobile applications and games. It is also allows small time programmers to publish and sell their mobile applications and games easily.